Macroeconomic determinants of trade openness: empirical investigation of SAARC region. Issue 2 (8th May 2018) - Tahir, Muhammad; Hasnu, SAF; Ruiz Estrada, Mario
Abstract : Purpose: Trade openness plays a significant role in the growth process of countries. The purpose of this paper is to examine the impact of macroeconomic determinants on the trade openness of countries. Design/methodology/approach: The study focuses on the South Asian Association for Regional Cooperation (SAARC) member countries and the data used were from 1971 to 2011. Panel data econometrics techniques and two stages least square method (TSLS) are used to carry out empirical analysis and robustness testing. Findings: The main finding of the paper is that macroeconomic determinants such as investment both in physical and human capital and per capita gross domestic product (GDP) positively affect trade openness. Further, the size of labour force and currency exchange rate has also impacted trade openness negatively and significantly. Practical implications: It implies that efficient macroeconomic management matters for higher trade openness. The sampled developing countries are suggested to pay favourable attention to macroeconomic variables if they want to grow in the long run through outward-oriented policies. Originality/value: This paper is an original contribution in the context of SAARC countries by focusing on the relationship between macroeconomic determinants and trade openness.